Model Gompertz pada Depresiasi Aset Kendaraan Mobil Honda Brio - Safitri, Oryza; Mikhratunnisa, Mikhratunnisa; Rizqi, Reza Muhammad (Politeknik Raflesia Press, 2024)
This study aims to determine how the Gompertz model can represent the depreciation of assets for the Honda Brio car. The research uses data on the value of the Honda Brio car, without considering the model series, from official Honda Indonesia websites and the OLX Indonesia online marketplace. The data collected includes the value of the Honda Brio from 0 years of use up to 7 years of use. The analysis results show that the Gompertz model can represent the depreciation of the Honda Brio vehicle asset for a usage period of 2 years, experiencing a decline of 7% to 13% from its initial price; for 5 years of use, a decrease of 19% to 29% from its initial price; for 10 years of use, a depreciation of 34% to 49% from its initial price; and for usage beyond 10 years, a depreciation of over 50%. The R Squared value of the model was found to be 93.36%. These findings provide insights for both the public and the government to make informed decisions and policies that are beneficial in addressing the depreciation of the Honda Brio vehicle asset..